Direct seeding and transplanting for rice production under flood-prone lowland conditions - Sharma, A.R. (Field crops research, 1995)
Rice productivity in flood-prone lowlands of South and Southeast Asia is low and highly variable. Ensuring good crop stands through optimal combinations of agronomic practices is important for improving yields. Present studies investigated the effect of various stand establishment practices, including vegetative propagation, under naturally flooded conditions (0–60 cm water depth) during 1992 and 1993 at Cuttack, India. Two popular rice cultivars, Gayatri (dwarf) and Matangini (tall), were either direct seeded in dry soil after premonsoon showers by early June using 400 and 600 seeds m −2 or transplanted after accumulation of water in the field in July–August using conventional nursery-grown seedlings and tillers uprooted from the direct-seeded crop. Direct-seeded crops showed better initial establishment and gave higher grain yield (3.23–3.53 t ha −1) as compared to transplanted crops (1.75–1.99 t ha −1) which were flooded at or soon after transplanting. Cultivar Gayatri was superior to Matangini, which lodged prematurely as the water level receded. The use of higher seed rate or uprooting of 70–90 rice plants m −2 did not affect the grain yield of direct-seeded crop adversely. Transplanted crop performed variably. Grain yield was higher with early transplanting in July in 1992 and with late transplanting in August in 1993. Transplanted crops grown from vegetative tillers yielded more (2.38 t ha −1) than those from nursery seedlings (1.36 t ha −1). Seedlings were shorter (51–68 cm) with less dry weight (0.51–0.80 g seedling −1) than vegetative tillers (73–100 cm, 0.99–1.58 g tiller −1) uprooted from direct-seeded rice which resulted in their better establishment in deep water. Water depth after transplanting and initial vigour of plants (height and dry weight) appeared to be the key factors in determining successful crop establishment and yield. The results suggest that in some flood-prone lowlands, where direct seeding could not be done earlier in the season, vegetative propagation using tall, vigorous tillers uprooted from the previously established direct-seeded crops is beneficial for greater productivity.